Djurägarbehandlingar inom renskötseln - Johansson, Andreas (2006)
The aim of this study was to document treatments of sick and injured reindeer in Tornedalen and the area around Gällivare. I also wanted to find out the basis for the treatments, how they are considered to work and if they agree with established veterinary science. The occurrence of "folk remedies" was especially studied. In all, 40 reindeer owners were interviewed. The interviews were conducted during the summer and autumn of 2005. The various diseases and injuries, which were described, can be divided into gastrointestinal, obstetric, parasitical, traumatic and miscellaneous categories. Most diseases and injuries were treated by the reindeer owners. The exception was bone fractures, which often led to euthanasia. Certain health problems (often related to feeding) were treated with simple management actions like changing the feed or moving the reindeer to new enclosures. Other reported treatments have probably been recommended by veterinarians, obtained from the literature or from other reindeer owners and farmers. Few cases of "folk remedies" were used. The reindeer owners, however, described several "folk remedies" that, according to them, had been used previously but were no longer in use. Treatment with ivermectin against parasites, mainly warble flies and nasal boots, was common. This is a reliable and effective measure to improve the health in the reindeer population. Syftet med denna undersökning var att kartlägga djurägarbehandlingar av sjuka och skadade renar i Tornedalen och området kring Gällivare kommun. Jag ville också ta reda på vad behandlingarna baseras på, hur de anses fungera och om de överensstämmer med etablerad veterinärmedicinsk kunskap. Förekomsten av så kallade ”huskurer” studerades särskilt. Sammanlagt intervjuades 40 renägare. Intervjuerna gjordes under sommaren och hösten 2005. De olika sjukdomarna och skadorna som renägarna beskrev kunde delas in i mag- och tarmsjukdomar, dräktighet/kalvning, parasiter, trauma och övriga åkommor. De flesta sjukdomar och skador som förekom ...